(untitled) (Journal of Population and Development, 2022)
This study attempts to explore the relationship between education and livelihood of Tamang people of residing Gokarneshwor municipality, Kathmandu district. Thirty six head of households have been selected by simple random sampling techniques and 4 by purposive. The quantitative and qualitative both data have been collected using structured questionnaires, interview and observation tools. The descriptive statistics was used to analyze the data. It was found that literacy rate of head of households was below the national literacy rate and literacy of all members of the family was above it. The access to natural capital was in diminishing trend. The livelihoods of Tamang people is still in traditional pattern. The average income of the households was found near to the national per capita income with no saving and Gini coefficient of income distribution was 0.269. There was positive relationship of education attainment with income and livelihoods of people. The sustainability of livelihoods of people has been found unsecured.